Using sign language in children with autistic spectrum disorders: special education teachers’ attitudes and experience - Eltyeb, Ebtihal Elameen; Taha, Seham Ali (International Journal of Research in Medical Sciences, 2023)
Background: There is evidence that sign language can help autistic children communicate more effectively. The present study aimed to assess the attitude and experience of special education school teachers toward sign language use in autistic spectrum disorder (ASD) and to explore the associated variables that influence positive attitudes. Methods: A cross-sectional study includes fifty-three teachers working with special education children. A conventional online survey was distributed to uncover the primary ideals of teachers’ attitudes toward using sign language by ASD children. The scores in the attitude domain were typically distributed and expressed as mean, then were categorized as poor (<50%), fair (50-69%), and good (≥70%). Results: More than 50 percent of the survey respondents have a level of education after graduation and 37% work in special needs education. Seventy-three percent of respondents had experience teaching ASD children, and more than half had less than five years of experience. However, about 73% received training courses in teaching ASD children, and only 37.7% had a good experience using sign language with ASD children. The overall percentage of good attitudes was 53%, which significantly correlates to gender and the number of students in the school. Conclusions: Even though sign language is a widely used form of communication for children with ASD, Sudan’s unique-education teachers still need support and training to instruct autistic students and caregivers how to use it. The teachers’ positive attitudes were significantly related to the teacher’s gender and the number of students per school.